2021
DOI: 10.1080/01402382.2021.1909964
|View full text |Cite
|
Sign up to set email alerts
|

Trust in government in Sweden and Denmark during the COVID-19 epidemic

Abstract: Did the different public-health policies that Sweden and Denmark pursued in the beginning of the COVID-19 pandemic result in different levels of public trust in governments' and health authorities' ability to guide the two countries safely through the pandemic? How did the level of trust change as the pandemic unfolded? And were there any cross-country differences in the correlates of trust? Using three original representative surveys conducted in Sweden and Denmark between late March and late June, 2020, this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
47
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(57 citation statements)
references
References 39 publications
8
47
0
2
Order By: Relevance
“…The Nielsen and Lindvall’s research (2021) in European nations such as Denmark and Sweden, as well as the Lim et al’s (2021) study in Singapore, showed that people’s faith in governments and health systems has led to attention to orders and the adoption of COVID-19 preventative behaviors. 33 , 34 In Iran, social capital is not at an adequate level, and government contact with the people is not a two-way street built on collaboration, trust, and harmony. This improper connection is aggravated by a lack of social adjustment.…”
Section: Discussionmentioning
confidence: 99%
“…The Nielsen and Lindvall’s research (2021) in European nations such as Denmark and Sweden, as well as the Lim et al’s (2021) study in Singapore, showed that people’s faith in governments and health systems has led to attention to orders and the adoption of COVID-19 preventative behaviors. 33 , 34 In Iran, social capital is not at an adequate level, and government contact with the people is not a two-way street built on collaboration, trust, and harmony. This improper connection is aggravated by a lack of social adjustment.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, nurses and midwives working in Denmark may have experienced less distress as they may have compared their situation to that in neighbouring countries and perceived it was not as severe. Danes also tend to have high levels of trust in their government and health authorities and consequently, the Danish nurses and midwives may have felt that the authorities had the pandemic under control ( Ministry of Foreign Affairs of Denmark, 2021 ; Nielsen & Lindvall, 2021 ). The distress levels of nurses and midwives in Australia may have been exacerbated by media reports of potential exposure to and high transmission rates of COVID-19 among health care workers internationally (ABC News, 2020a ; Morris, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…8 9 This is partly due to Denmark being historically a high trust country, which in turn is partly a product of a long standing commitment to reducing inequalities and providing strong welfare protections, but also partly due to the decisive implementation of strong pandemic protections. 8 Building people's trust in government, and building a government that trusts its people, is a long term investment for the next pandemic.…”
mentioning
confidence: 99%